The Effect of Market Share Distribution on Industry Performance - Kwoka, John E. (The Review of Economics and Statistics, 1979)
A central proposition of industrial organization is that the size distribution of sellers is an important determinant of an industry's profitability. Numerous studies have explored -and generally confirmed-such a relationship, but virtually all have been subject to a serious and binding constraint. The lack of individual market share data has forced use of the simple sum of the four (or eight) largest shares, i.e., the concentration ratio, as the variable representing firm size distribution. Nothing in theory, however, predicts that exactly four firms are crucial to industry performance, and nothing implies that they are equally important, as is implicit in their simple summation. The availability of market share data for 19721 avoids the necessity of any such assumptions in this research. Instead, we begin by recognizing two fundamental and opposing forces within industries-the advantages of greater output control by leading firms, and the difficulty of agreement among more numerous firms. At least potentially, output control confers the power to set and enforce above-competitive prices for the benefit of the industry. Much depends, however, on who controls output, since the number of core' firms influences the strength of collusive or cooperative agreements (Scherer, 1970, pp. 183-186). Large numbers reduce the likelihood of agreement but, ceteris paribus, provide control over greater industry output. These factors are suggested in both theory and previous empirical work. Thus, the Cournot, Chamberlin (1933), and Stigler (1964) theories of oligopoly imply that fewness of firms, size disparity, and threshold levels of output control are crucial. Empirical testing has been limited by published concentration ratios but nonetheless has produced some relevant insights. The fourfirm concentration ratio proves to be more closely correlated with industry performance than the eight-firm or more inclusive versions (e.g.. Kilpatrick, 1967), suggesting the importance of quite small numbers. Various efforts to capture size inequality have demonstrated close associations with above-competitive profitability and can also be interpreted as emphasizing the role of the top few firms (Stigler, 1964; Miller, 1967; Mann, 1970; Kwoka, 1977). And a critical level of outpuit control often, but not always, seems to emerge in the vicinity of 50% for four firms (e.g., Rhoades and Cleaver, 1973; White, 1976). But much of interest about firm size distribution is inevitably obscured by the concentration ratio aggregate. In contrast, the present data permit detailed examination of the market share correlates of industry performance, casting light on the questions of what number of firms is too large for collusion and what amount of output control is 'sufficient for price-setting power. We shall demonstrate basic deficiencies of the conventional concentration ratio, complex roles for muiltiple shares in industry performance, and a greater overall importance for large-share firms than heretofore recognized.